Physical Activity as a Factor to Improve the Quality of Student Life - M. M. Kolokoltsev; S. S. Iermakov; N. V. Tretyakova; V. L. Kraynik; E. V. Romanova (Obrazovanie i Nauka)
Introduction. Nowadays, the specialists note a steady decrease in the level of physical, somatic and mental health of modern student’s youth due to intensive computerisation of the educational space, high teaching loads, increased time for self-training, change of social environment and violations of the basic rules of a healthy lifestyle. In order to prevent the negative consequences of these processes in terms of health preservation and improvement of the situation, it is necessary to identify and follow the trends in young people’s quality of life concerning their physical activity, which is an important condition for harmonious development, especially during the period of youth ontogenesis.The aims of the present research were the following: to study the indicators of well-being of senior students of technical specialties and to determine the vector of changes in graduates’ quality of life depending on the degree of their motor activity.Material and research methods. When employing the Russian-language version of the Short Form (36) Health Survey, the students (n = 286) of Irkutsk National Research Technical University (Russia) were examined on a phased basis (7-year time gap). In the course of monitoring procedures, the method of questionnaire surveys was used. The comparison of the obtained data on the physical condition of students of different generations was carried out through comparative analysis. The validity of differences was determined by calculating the Student’s t-test.Results and scientific novelty. The prolonged survey showed that physical activity of girls decreased by 15.2%, boys - by 15.7% in 2019 compared to 2012. The general state of students’ health condition deteriorated (by 22.5% in girls, by 21.3% in boys). The values of indicators such as “role functioning”, “pain intensity”, “mental health”, “emotional state”, “social and life activity” fell substantially. There was a decreased in the number of students, who observe the regulations, recommended by the World Health Organisation for weekly motor activity. Hypodynamia was diagnosed in undergraduates, who have completed an elective course in physical culture and sports. These facts result from the decrease in the number of students motivated to keep a healthy lifestyle and regularly do physical exercises, as confirmed by the students’ questionnaire answers. More than 21% of respondents surveyed that they felt healthy, and therefore they had no need to take care of their well-being; 37.4% of respondents lack the willpower to stay in shape, and 33.9% mentioned that there was no time for physical education. Although interviewees appreciated the importance of physical activity in people’s daily activities, only 30% visited sports sections and only 14% had a morning workout. It is highlighted that in order to preserve the physical and mental health of the nation, the valeological education of students should become a priority in higher educational institutions.Practical significance. The current research findings can serve as the basis for the cooperation of pedagogical technologies of physical education in universities, for the provision of recommendations for the corresponding independent classes of students, and for the organisation of hypodynamia preventive actions. A combination of these measures will contribute to improving the health and quality of life of future professionals.